A new species of Henneguya, a gill parasite of Astyanax altiparanae (Pisces: Characidae) from Brazil, with comments on histopathology and seasonality - Barassa Bianca; Cordeiro Nelson S; Arana Sarah (Memorias do Instituto Oswaldo Cruz, 2003)
A new species of Myxosporea, Henneguya chydadea, is described parasitizing the gills of Astyanax altiparanae collected from a lake on Rio das Pedras farm near Campinas, state of São Paulo, Brazil. Of the fish examined, 88.3% had gills parasitized by myxosporeans. The prevalence of the parasite ranged from 80% in the spring and fall, 93% in the summer and 100% in the winter. The parasite induced the formation of white, oval-shaped cysts measuring 40-64 µm x 64-80 µm which deformed the gill lamellae, compressed the capillaries, and caused retraction of the neighboring lamellae. The mature spores were elongated and had two identical, parallel elongate polar capsules. Each capsule contained a polar filament with 9-10 turns. There was no mucous envelope or iodinophilous vacuole. Morphometric differences between this parasite and other species of the genus Henneguya indicated, that he parasite observed in A. altiparanae is a new species. This is the first report of a myxosporeanparasitizing A. altiparanae.